Langkah Penyusunan dan Analisis Butir Soal Hots (Higher Order Thinking Skills) pada Mata Pelajaran Pendidikan Agama Islam (PAI) dan Budi Pekerti - Indri Sari; Danil Usama; Dwi Noviani; Firdaus Basuni (Universitas Katolik Widya Karya Malang, 2023)
Questions with a high level of thinking level or what is often referred to as HOTS usually provide unusual word choices and require advanced vocabulary and/or appropriate contextual understanding of the meaning of a word depending on its use in a sentence. In this problem, prepositions can also be classified as difficult questions because they are not only interpreted literally, but also require exposure to those words beforehand, especially in phrasal verbs or phrasal adjectives. The purpose of the HOTS model questions is to encourage students to do high-level reasoning so that they are not fixated on only one pattern of answers resulting from the memorization process, without knowing the concept of knowledge. HOTS is one of the skills demands in 21st century learning, namely critical, creative, collaborative, and communicative thinking. HOTS questions make it possible to create the same type of questions, but with different questions. This aims to capture quality students who are in accordance with the development of information technology in the digital era. By familiarizing yourself with challenging questions, your potential can also be encouraged to further develop.